2020
DOI: 10.1371/journal.pone.0241977
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the integration of tuberculosis screening and contact investigation in tuberculosis clinics in Ethiopia: A mixed method study

Abstract: Background Aligned with global childhood tuberculosis (TB) road map, Ethiopia developed its own in 2015. The key strategies outlined in the Ethiopian roadmap are incorporating TB screening in Integrated Maternal, Neonatal and Child Illnesses (IMNCI) clinic for children under five years (U5) and intensifying contact investigations at TB clinic. However, these strategies have never been evaluated. Objective To evaluate the integration of tuberculosis (TB) screening and contact investigation into Integrated Mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 32 publications
1
8
0
1
Order By: Relevance
“…46 Many studies described multifaceted interventions and interventions were heterogeneous ( Table 1 ; available at: https://www.who.int/publications/journals/bulletin/ ). The primary intervention was decentralization for 23 studies, 19 – 39 , 44 , 46 integration for three studies 40 , 41 , 45 and family-centred care for two studies. 42 , 43 Because of the small number of studies of integrated and family-centred care models, we incorporated into the evidence synthesis 19 additional studies without comparative outcomes (six studies reporting on integrated models 47 – 52 and 13 studies reporting family-centred models; 53 65 Table 2 ; available at: https://www.who.int/publications/journals/bulletin/ ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…46 Many studies described multifaceted interventions and interventions were heterogeneous ( Table 1 ; available at: https://www.who.int/publications/journals/bulletin/ ). The primary intervention was decentralization for 23 studies, 19 – 39 , 44 , 46 integration for three studies 40 , 41 , 45 and family-centred care for two studies. 42 , 43 Because of the small number of studies of integrated and family-centred care models, we incorporated into the evidence synthesis 19 additional studies without comparative outcomes (six studies reporting on integrated models 47 – 52 and 13 studies reporting family-centred models; 53 65 Table 2 ; available at: https://www.who.int/publications/journals/bulletin/ ).…”
Section: Resultsmentioning
confidence: 99%
“…We identified three comparative studies where integration was the primary intervention ( Table 4 ). 40 , 41 , 45 A stepped-wedge trial in Ethiopia showed that screening in integrated maternal, neonatal and child illnesses clinics increased tuberculosis diagnoses among children (0.5; 95% CI: 0.2–0.7; additional cases per clinic per 4-month period). 41 A pre-post study from Zambia showed that having antiretroviral services and tuberculosis services in the same health facilities led to increased case notifications in the 0–14 year age group (IRR: 2.67; 95% CI: 1.05–6.76).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the variation in country-specific settings, and the variety of settings within countries, the NTP should consider a flexible approach guided by the existing infrastructure, availability of resources and disease burden -for example, decentralization of a single component of TB services versus a combination of components; phased implementation versus full-scale implementation; or operational research setting versus programmatic implementation. Some studies have shown that interventions delivered at the primary health facility and community levels (combined) have resulted in increased TB case notifications and TPT initiations compared with more centralized approaches (158)(159)(160)(161)165).…”
Section: Regulatory Framework and Policy Guidancementioning
confidence: 99%
“…Efforts in high-burden settings to integrate TB screening into primary care settings such as outpatient clinics and IMNCI clinics have been shown to increase the referral of children at risk of TB, as well TB case detection [12,47]. The ongoing multi-country Catalyzing Pediatric TB Innovations (CaPTB) project has undertaken the systematic integration of TB screening and strengthening of decentralized diagnostic capacity at different service delivery entry points, including outpatient, inpatient, well-child, nutrition, and HIV clinics.…”
Section: Integrating Tb Care With Other Services For Children and Ado...mentioning
confidence: 99%